Somatosensory evoked potentials in workers exposed to toluene and styrene - Stĕtkárová, I; Urban, P; Procházka, B; Lukás, E (British journal of industrial medicine, 1993)
Somatosensory evoked potentials (SEPs) were used to evaluate possible subclinical impairment of the nervous system due to occupational exposure to toluene and styrene. A group of 36 rotogravure printers with severe exposure to toluene, 20 workers with severe exposure to styrene in a glass laminate manufacturing plant, and a comparison group of healthy subjects were studied. The severity of exposure was documented by measurements of toluene and styrene concentrations in breathing zone air, by hippuric acid concentration in urine in the group exposed to toluene, and by urinary mandelic acid concentration in the group exposed to styrene. Somatosensory evoked potentials were measured by stimulation of the median nerve at the wrist and the tibial nerve at the ankle. Peripheral conduction velocities (CVs) in both extremities and central conduction time (CCT) after tibial nerve stimulation were significantly decreased in both exposed groups. Significantly prolonged latencies of peripheral and cortical SEPs to median nerve stimulation as well as cortical SEPs to tibial nerve stimulation were found in workers exposed to styrene. Some abnormalities in SEPs at peripheral or spinal and cortical levels were found in eight workers exposed to toluene and six workers exposed to styrene. Of these, in three workers exposed to toluene and two to styrene increased CCT and delayed latencies of cortical responses at normal conduction values in the periphery were found. A trend for increased frequency of abnormal SEPs with duration of exposure to toluene and styrene and alcohol abuse was found. Abnormalities in SEPs in the exposed groups are most probably of multifactorial origin. Central SEP abnormalities in both exposed groups could indicate early signs of subclinical dysfunction at spinal and cortical levels and could be due to toluene or styrene exposure probably potentiated by alcohol consumption in the group exposed to toluene.
Keywords: Styrenes; Occupational Exposure; Humans; Evoked Potentials, Somatosensory; lidé středního věku; Occupational Diseases; Nervous System Diseases; Female; Aged; dospělí; nemoci z povolání; Toluene; senioři; vzduch; lidé; Air; časové faktory; toluen; Adult; ženské pohlaví; somatosenzorické evokované potenciály; Male; Middle Aged; styreny; pracovní expozice; nemoci nervového systému; mužské pohlaví; Time Factors